Adolescents' views on high school food environments. (14th October 2020) - Ronto, Rimante; Carins, Julia; Ball, Lauren; Pendergast, Donna; Harris, Neil
Abstract: Issue addressed: This study explored adolescents' views on high school food environments and potential strategies to help them to make informed food choices. Methods: Fifteen focus groups were conducted with 131 adolescents aged 12‐17 years from three high schools in South East Queensland, Australia. Adolescents were asked how their school food environment (dis)encouraged them to eat healthy and what schools could do to help them eat healthier. All focus groups were audio recorded. Data were analysed using content and thematic data analysis methods. Results: Four major themes emerged: food availability and affordability; food related policy and regulations; nutrition education; and attitudes, preferences and practices. Adolescents stated that nutrition education within the school curriculum and positive role modelling by peers and school staff in healthy eating were the major factors in helping them to make informed food choices. In contrast, high availability, affordability, fundraising, peer pressure, positive attitudes and negative role modelling towards unhealthy foods impacted unhealthy dietary behaviours. Conclusions: Emerging results indicate that adolescents do not perceive the current high school food environments as helping them to make healthy food choices. Adolescents suggested limiting unhealthy foods in high schools by implementing strict food and beverage policies, compulsory nutrition education classes and changing attitudes towards healthy foods as strategies to improve high school food environments. So what?: This study highlights the importance of high school food environments in impacting adolescents' food choices. Strategies identified by adolescents inform public health practitioners and school authorities on how high school food environments could be tailored to help them in making better food choices.